PENGENALAN PENCATATAN AKUNTANSI KEPADA PEDAGANG KECIL DI WILAYAH PANTAI KUTA KEK MANDALIKA - Syukri, Muhammad; Fitri, Syarifah Massuki; Faezal, Faezal; Utami, Luh; Rizqina, Intan; Nurlailah, Nurlailah (LPPM Institut Pendidikan Nusantara Global, 2024)
Small traders are part of an economic life that deserves attention, through the sale of food, drinks to accessories on the beachside it has an impact on increasing individual income related to existing problems, the obstacles faced by small traders are the lack of capital and debts that are always increasing not proportional to the income earned, with this Community Service activity carried out to provide motivation and information about accounting and accounting records to small traders to be able to develop their business. The implementation method is carried out in three stages, namely, the first stage of observation and interviews regarding the problems faced by traders on the beach, the second stage of determining the implementation plan and the division of tasks to the Community Service team, the third stage of implementation with methods, namely, the first lecture and presentation method, the second with the question and answer method, and the last is the method of assistance in making accounting records. The results of this Community Service activity provide new information about accounting and recording for small traders where the traders participate in activities happily and are starting to be interested in recording in developing their business which has never been done, this is also because many small traders sell on the beach without sufficient provisions, not because they don't want to but because they don't want to do it.